Nilai Sosial dan Ekonomi Tradisi Ngalak Anak di Pulau Gili Kabupaten Probolinggo - Rofiq, Zainur; Ganefo, Akhmad (University of Jember, 2016)
Abstract This study discusses the existence of social and economic value that occurs in “Child Adoption” tradition at Gili Ketapang Probolinggo. The method that is used in this study is ethnometodology approach with a qualitative descriptive research. The informants are living at Gili that take care of other peoples’ children. The sampling method used is purposive sampling and snowball sampling. The results shows that there are social and economic orientation in a family when they take care of his brother's child or their neighbors’s children and also other people's children. The tradition of adoption at Gili is not the same as adoption that gives a clear position of children’s status as their own children. In that tradition, there is a cost and reward that will be a consideration between foster parents and biological parents. The Social value in this tradition are the basic thought that they take care others people’s children because they want to help for children’s prosperity and also they want to get some benefits from the children biological parents’ opulence.